Technology Perceptions in MSMEs Islamic P2P Lending Intentions: The Moderating Role of Religiosity - Febri Khoiriana; Sunarmo (Jurnal Manajemen dan Bisnis Madani, 2026)
This study examines how technology perceptions influence MSMEs’ intention to use Islamic peer-to-peer (P2P) lending by analyzing the roles of Islamic financial literacy, perceived ease of use, perceived usefulness, and perceived risk, with religiosity as a moderating variable. Using a quantitative approach, data were collected from 100 MSME owners in DKI Jakarta and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) with WarpPLS 7.0. The results indicate that Islamic financial literacy, perceived ease of use, and perceived usefulness have positive and significant effects on MSMEs’ intention to use Islamic P2P lending, while perceived risk has a significant negative effect. Furthermore, religiosity is found to moderate the relationships between Islamic financial literacy and perceived usefulness with intention to use Islamic P2P lending. However, religiosity does not moderate the effects of perceived ease of use and perceived risk on intention to use. These findings contribute to the literature on Islamic fintech adoption by highlighting the joint role of technological perceptions and individual religiosity in shaping MSMEs’ intentions to use Islamic P2P lending. The study also offers practical implications for policymakers and regulators in strengthening Islamic financial literacy and developing supportive regulatory frameworks for Islamic fintech. In addition, Islamic P2P lending providers are encouraged to enhance platform usability, service benefits, and security to increase MSME adoption.